Mental reality in cognitive cience - Medina, Nicolas (2010)
The aim of this paper is to show the objective nature of the mind describing their natural properties that should have causal powers to make an impact on physicals organisms. Arguments of this paper follow the cognitive view that recognize the mind as a symbolic representational and computational entity, defended by Jerry Fodor.